The role of digital financial inclusion in China on urban—rural disparities in healthcare expenditures - Zhang, Yuyang; Li, Keyi; Pang, Yumeng; Coyte, Peter C. (Frontiers in Public Health, 2024)
The digital financial inclusion (DFI) provides opportunities to improve the relative capacity to pay for healthcare services by rural residents who are usually underserved by traditional finance in China. This paper provides empirical evidence on how the development of DFI affects the healthcare expenditure disparities between urban and rural residents.We employed the fixed effects model and instrumental variable method to estimate the impact of DFI on the Theil index of urban-rural disparities in healthcare expenditures, using panel data from 31 provinces (2011 2020) in China. We further adopted a moderating effect model to test whether the intensity of the impact would vary depending on the level of local government health expenditures.The results suggest a negative association between the development level of DFI and the urban-rural healthcare expenditure disparities in China. For every 1% increase in the DFI index, the Theil index of urban-rural disparities in healthcare expenditures would fall by 0.0013. After changing the measurement method for the dependent variable and adjusting the sample, the results remain robust. Moreover, the result of the moderating effect model indicates that, a high level of government health expenditures is conducive to the impact of DFI.Discussion: Our research reveals that DFI plays an important role in bridging the urban-rural gap in healthcare expenditures. This finding provides new information for addressing the issue of urbanrural healthcare inequality in China. Chinese government needs to accelerate the construction of digital infrastructure and increase the penetration rate of digital tools in rural areas to promote the beneficial effects of DFI.